Using the computer mouse for stress measurement – An empirical investigation and critical review. Issue 145 (January 2021) - Freihaut, Paul; Göritz, Anja S.
Highlights: The computer mouse might be an ubiquitous, unobtrusive and cheap sensor for stress measurement. Data from a laboratory study reveal no clear generalized relationship between mouse usage and stress. The results challenge the state-of-the-art in the young research field and provide the basis for more thorough future research attempts. Abstract: The present study investigates the potential of measuring a person's stress level by their computer mouse usage. This measurement approach is based on the assumption that cognitive and physiological changes due to stress do manifest in measurable psycho-motor changes when using the mouse. We conducted a within-participant laboratory experiment in which we captured the mouse usage of N = 53 participants during four tasks in a high-stress and a low-stress condition. Although self-report as well as physiological data indicated successfully manipulated differences in stress level between the conditions, we failed to find clear differences in mouse usage as a function of stress level. Theoretical as well as methodological challenges of the research area, which emerged from the results, are discussed.